Good documentation practices: UM experience - Fong, M.Y.; Kiran, K.; Nik Ahmad, Kamal; Suzeini, A.H. (2007)

(untitled)
This paper discusses the requirement of documentation system in the context of higher education. The characteristic of a document system should include proper control, relevant, dynamic, currency, accessibility, scope, ownership / authority, record. At University of Malaya (UM) the document system encompass all documents which are required under the MS ISO 9001:2000 and organizational needs. Currently, it consists of a Quality Manual, 30 Quality Procedures and 428 Work Instructions, 32 Document Specifications, 4 Guide Lines and Quality Records. Initially these documents were in printed format and CD ROM and were distributed manually to the respective departments and units. Due to logistic and economic reasons, the documents were converted into electronic format, first in pdf format and finally as hypertext format (html). An E-document System has many advantages. First, it ensures the availability of documents to all staff and students at any time. These documents can be accessed without the need of any specific software or operating system. Accessibility is through any computer within the campus that has an Internet connection. Challenges to the documentation are manifold. In the wake of major changes introduced by management and supporting services, the system has to respond rapidly in keeping up to the needs of the documentation. Process owners should be given access to amend documents online in order to speed up dissemination of information and new or amended procedures to the campus. Relevant or critical documents such as course pro-forma and curricula have to be centralized as measures as an authorized source of reference.